2020
DOI: 10.7717/peerj.8139
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure of Australian glass shrimp,Paratya australiensis,in relation to altitude

Abstract: Paratya australiensis Kemp (Decapoda: Atyidae) is a widely distributed freshwater shrimp in eastern Australia. The species has been considered as an important stream organism for studying genetics, dispersal, biology, behaviour and evolution in atyids and is a major food source for stream dwelling fishes. Paratya australiensis is a cryptic species complex consisting of nine highly divergent mitochondrial DNA lineages. Previous studies in southeast Queensland showed that “lineage 4” favours upstream sites at hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
(90 reference statements)
0
5
0
Order By: Relevance
“…Influence of elevation on Paratya population was reported by Cook et al (2006) who mentioned that Paratya populations were isolated by steep stream gradients among the upland sites and between upland and lowland sites in Granite Creek in Victoria. Also, Rahman et al (2020) found highest genetic differentiation between high-elevation and low-elevation populations (Paratya) in Booloumba Creek in Queensland. So, there is evidence for influence of elevation on Paratya populations.…”
Section: Discussionmentioning
confidence: 92%
“…Influence of elevation on Paratya population was reported by Cook et al (2006) who mentioned that Paratya populations were isolated by steep stream gradients among the upland sites and between upland and lowland sites in Granite Creek in Victoria. Also, Rahman et al (2020) found highest genetic differentiation between high-elevation and low-elevation populations (Paratya) in Booloumba Creek in Queensland. So, there is evidence for influence of elevation on Paratya populations.…”
Section: Discussionmentioning
confidence: 92%
“…Paratya spp. are the most widespread atyid freshwater shrimp in eastern Australia, found in upland and lowland streams, dams and retention ponds, with distribution from southern Queensland to eastern South Australia (Cook et al 2006;Rahman et al 2020). Prior to a reclassification by Suter et al (2022), it was believed that only a single highly variable Paratya species (Paratya australiensis) occurred in Australia.…”
Section: Study Species Collection and Acclimatisationmentioning
confidence: 99%
“…Temperature is the most critical factor influencing the breeding season of Australian Paratya spp., with hydrology a secondary influence (Hancock and Bunn 1997). In contrast to the tropical regions, the breeding season of Paratya in temperate and subtropical regions is confined to the warm summer months (Hancock and Bunn 1997;Rahman et al 2020). Paratya spp.…”
Section: Study Species Collection and Acclimatisationmentioning
confidence: 99%
See 2 more Smart Citations